A case of failed eradication of cystic fibrosis-related sinus colonisation by Pseudomonas aeruginosa. Issue 1 (December 2015) - Linnane, Barry; Kearse, Linda; O' Connell, Nuala; Fenton, John; Kiernan, Miranda; Dunne, Colum
Abstract Background Pseudomonas aeruginosa is a pathogen associated with cystic fibrosis that has potential to decrease lung function and cause respiratory failure. Paranasal sinuses are increasingly recognised as potential reservoirs for intermittent colonisation byP. aeruginosa . This case documents investigation and outcome ofP. aeruginosa recurrence in a male paediatric patient over an eight year period. Case presentation A 12 year old Irish male paediatric cystic fibrosis patient experienced intermittent culturing ofP. aeruginosa from the oropharyngeal region, indicating chronic infection of the sinuses despite absence of symptoms, retaining good lung function, and normal bronchoscopy and bronchoalveloar lavage. However, P. aeruginosa was isolated from a sinus wash-out and was identified as a unique strain ofP. aeruginosa that was also cultured from cough swabs. Despite treatment, successful eradication from the paranasal sinuses was not achieved. Conclusions Few reports have addressed the paranasal sinuses as a reservoir for lung infection in cystic fibrosis patients despite increased recognition of the need to investigate this niche. In this case, attempts at eradication ofP. aeruginosa present in paranasal sinuses including oral and nebulised antimicrobials proved unsuccessful. However, detection ofP. aeruginosa in the paranasal sinuses instigated antimicrobial treatment which may have contributed to prevention of migration to the lower airways. Our outcome provides additional insight and may indicate utility of nasal lavage or nasal endoscopy in paediatric cystic fibrosis patients' annual review clinic visits.